Trophic Position of the Species and Site Trophic State Affect Diet Niche and Individual Specialization: From Apex Predator to Herbivore - Vejřík, Lukáš; Vejříková, Ivana; Blabolil, Petr; Sajdlová, Zuzana; Kočvara, Luboš; Kolařík, Tomáš; Bartoň, Daniel; Jůza, Tomáš; Šmejkal, Marek; Peterka, Jiří; Čech, Martin (Biology, 2023)
Intra-species variability in isotopic niches, specifically isotopic total niche width (ITNW), isotopic individual niche width (IINW), and isotopic individual specialization (IIS), was studied using an innovative approach without sacrificing the vertebrates. Stable isotopes (δ13C, δ15N) in four body tissues differing in isotopic half-life were analyzed from four freshwater fish species representing different trophic positions. ITNW was widest for the apex predator (European catfish) and narrowest for the obligate predator (Northern pike). IINW exhibited a polynomial trend for the European catfish, Northern pike, and Eurasian perch (mesopredator), decreasing with body mass and increasing again after exceeding a certain species-dependent body mass threshold. Thus, for ectotherms, apex predator status is linked rather to its size than to the species. In herbivores (rudd), IINW increased with body mass. The IIS of predators negatively correlated with site trophic state. Therefore, eutrophication can significantly change the foraging behavior of certain species. We assume that the observed trends will occur in other species at similar trophic positions in either aquatic or terrestrial systems. For confirmation, we recommend conducting a similar study on other species in different habitats.
Keywords: stable isotope analysis; freshwater ecosystem; niche width; isotopic half-life; aquatic food web